Trends, Volatility, and Growth in UM-PTKIN Admissions: Strategic Implications for State Islamic Higher Education Institutions - Widi Cahya Adi; Miftahussadi’ah; Muhamad Rahman Bayumi; Oki Sapitri Menghayati (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study examines trends, growth, and volatility in UM-PTKIN admissions as strategic indicators of institutional adaptability within Indonesia’s State Islamic Higher Education system. Using longitudinal administrative data from 2022 to 2025, the study applies a quantitative descriptive–comparative approach to analyze admissions dynamics across different types of State Islamic Higher Education Institutions, namely State Islamic Universities (UIN), State Islamic Institutes (IAIN), and State Islamic Colleges (STAIN). Admissions performance is assessed through a horizontal trend index, compound annual growth rates (CAGR), and year-to-year volatility measures. The findings reveal a persistent national-level contraction in UM-PTKIN participation, indicating structural pressures affecting centralized admissions pathways. However, institutional-level analysis demonstrates pronounced heterogeneity. UIN institutions experience the sharpest decline, characterized by negative growth and high volatility, reflecting heightened exposure to national competition. IAIN institutions display mixed but relatively resilient trajectories, while STAIN institutions exhibit strong positive growth and sustained upward trends, despite overall system-level contraction. Volatility patterns further indicate that admissions instability is closely linked to institutional positioning rather than institutional scale alone. These results suggest that UM-PTKIN admissions dynamics function as strategic signals of enrolment governance capacity rather than as isolated performance outcomes. The study contributes to enrolment management and institutional differentiation literature by extending these frameworks to faith-based public higher education contexts. Policy implications highlight the need for differentiated enrolment governance strategies that recognize institutional heterogeneity to support sustainable admissions planning within Indonesia’s Islamic higher education system.